Wittgenstein: Mystical That the World Exists - Dainys, Augustinas (Problemos, 2003)
The article discusses aphorisms of Wittgenstein's „Tractatus Logico-Philosophicus“ related to the issue of mysticism. It considers their place in the „Tractatus“ in general. lt analyses how they turn the „Tractatus“ into an exceptional work of philosophy of language. The „Tractatus“ has two sides; while one discusses one side, she has to remain silent about the other side. The relationship between natural science and mystical perspectives is analysed. It is demonstrated that the „Tractatus“ is written from the transcendental perspectíve, i. e. looking at the world from outside, just like the Lord does it. Platonism of the „Tractatus“ and emerging problem of the third person is discussed. The dehumanising tendency of Wittgenstein's outlook and the possible totalitarian implications are disclosed.
Keywords: world; natural science; mystical; transcendence; showing